2020
DOI: 10.26434/chemrxiv.9995078.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiphase Complex Coacervate Droplets

Abstract: Liquid-liquid phase separation plays an important role in cellular organization. Many subcellular condensed bodies are hierarchically organized into multiple coexisting domains or layers. However, our molecular understanding of the assembly and internal organization of these multicomponent droplets is still incomplete, and rules for the coexistence of condensed phases are lacking. Here, we show that the formation of hierarchically organized multiphase droplets with up to three coexisting layers is a generic ph… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(83 citation statements)
references
References 50 publications
5
78
0
Order By: Relevance
“…It is therefore important to bear in mind that in vitro systems with few components may tend toward multiple phases at a lower interaction difference than would actually be found in the complex multi-component cellular environment. Experimentally both Mountain and Keating and Lu and Spruijt 48,49 showed for a three-component system, say two polycations and a single polyanion, that, where some sufficient interaction strength difference between polycations exists, two phases will form with the shared oppositely charged polymer unequally distributed between the two phases based on relative interaction strength. Lu and Spruijt calculate the magnitude of this sufficient difference from density, which they extrapolate from a difference in critical salt concentration 49 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is therefore important to bear in mind that in vitro systems with few components may tend toward multiple phases at a lower interaction difference than would actually be found in the complex multi-component cellular environment. Experimentally both Mountain and Keating and Lu and Spruijt 48,49 showed for a three-component system, say two polycations and a single polyanion, that, where some sufficient interaction strength difference between polycations exists, two phases will form with the shared oppositely charged polymer unequally distributed between the two phases based on relative interaction strength. Lu and Spruijt calculate the magnitude of this sufficient difference from density, which they extrapolate from a difference in critical salt concentration 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that the miscibility of distinct phases of hydrophobic elastin-like polypeptides can be regulated by sequence changes that alter the critical temperature of phase separation 47 . More recent works have shown that coexisting phases of charged polyelectrolytes can, when sufficiently different, form multiple phases 48,49 . Where there is a difference in critical salt concentration, which is indicative of a different density and water content between complex coacervates, multiple phases will form.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-phasic structures, which stem from the coexistence of multiple immiscible liquid phases [50][51][52] , are hallmarks of several subcellular biomolecular condensates such as the nucleolus and stress granules 11,14,53 . For a three-phase-system (such as A-droplets, Bdroplets, and C-dispersed liquid phase), the equilibrium spatial configuration is determined by the relative interfacial tensions (AC, BC, and AB) of the three liquid phases 11,15,16 . Based on the rank order of AC, BC, and AB, three configurations are possible ( Fig.…”
Section: Mixture Composition Tunes the Topology Of Coexisting Pld Andmentioning
confidence: 99%
“…Mounting evidence now suggest that the spatial organization of biomolecules into distinct sub-compartments within BMCs [e.g., nuclei 10,11 , nuclear speckles 12 , paraspeckles 13 and stress granules 14 ] adds another layer of internal regulation of composition and plays a fundamental role in facilitating their complex biological functions. These mesoscopic multilayered structures can be qualitatively understood on the basis of a multi-phasic condensate model, where two or more distinct types of partially immiscible condensed phases are formed by spontaneous phase separation of individual components in a multi-component mixture 11,15,16 . However, due to the complexities generated by the presence of a large number of distinct protein and RNA components in a typical intracellular BMC, the underlying molecular mechanisms that regulate the multiphasic condensate composition and spatial organization remain largely unexplored.…”
mentioning
confidence: 99%